(3TQM Cdajg GHf eGdcs - (3CHh ESMGb EHQGgje Hf ehSi Hf eMeO GddNei GdTGWHis; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3YeQ Hf YHO Gddg GdefXQGhi s)
(3ChdgG (B:s
(3jHOC HTQM bhd GHf eGdc , ef HGH YhGed GdLRe (B: (3hGdCeQ Ef cGf HZjQ CaYd adG JfUH LhGHg hLReg CbHdG s
(3BNQgG (B:s
(3jfJgi HTQM bhd GHf eGdc , ef BNQ HGH GdfSH (B: (3hZjQ eG CSdaJ ebQQkG Ydi GdPi jfbd ajg EbJUQG s
(3fSNI ebGHdIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs